2017
DOI: 10.1002/jsfa.8553
|View full text |Cite
|
Sign up to set email alerts
|

Physical compatibility between wax esters and triglycerides in hybrid shortenings and margarines prepared in rice bran oil

Abstract: The addition of 1.0%wt sunflower wax enhanced the solid content and network strength of hybrid palm-based shortenings. Sunflower wax helped to stabilise the water droplets inside the wax-based crystalline network without flocculation during shear-cooling. This research provides fundamental insight into the structuring of hybrid systems containing waxes, which could be interesting for the production of low-saturated fat products in the food industry. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…Sunflower wax (SW) is located mainly in the hulls of the seeds (80–83% of the total wax content), the wax content concentration being up to 3–4% depending on the genotype of the seeds, the geographic origin, and the maturity stage of the plant from which the wax was obtained, amongst other factors . Sunflower wax is considered as an alternative to rice bran, carnauba, and candelilla wax, and has multiple potential uses, including the production of edible films to act as coatings to extend the shelf life of food products, and the ability to structure vegetable oils to form oleogels and emulsions . Due to the purity of its chemical composition, SW has its own functional characteristics, showing stronger gelling capacity, and improving oil binding and lubricating capacity at lower concentrations than other vegetable waxes .…”
Section: Introductionmentioning
confidence: 99%
“…Sunflower wax (SW) is located mainly in the hulls of the seeds (80–83% of the total wax content), the wax content concentration being up to 3–4% depending on the genotype of the seeds, the geographic origin, and the maturity stage of the plant from which the wax was obtained, amongst other factors . Sunflower wax is considered as an alternative to rice bran, carnauba, and candelilla wax, and has multiple potential uses, including the production of edible films to act as coatings to extend the shelf life of food products, and the ability to structure vegetable oils to form oleogels and emulsions . Due to the purity of its chemical composition, SW has its own functional characteristics, showing stronger gelling capacity, and improving oil binding and lubricating capacity at lower concentrations than other vegetable waxes .…”
Section: Introductionmentioning
confidence: 99%
“…Sunflower wax Rice bran oil 1 (Doan, Tavernier, Danthine, et al, 2018) Water-in-oil emulsion oleogels showed desirable spreadable properties due to the low viscosity of oil gel at the baking temperature. Yılmaz and Öğütcü (2015a) compared physicochemical, sensory, and storage stability properties of cookies prepared with SW and BW oleogels of hazelnut oil against cookie made with the commercial shortening.…”
Section: Baked (Pastry) Productsmentioning
confidence: 99%
“…The influence of SW as a costructurant in 20% W/O emulsions (margarines) was investigated by Doan, Tavernier, Danthine, Rimaux, and Dewettinck (2018). Fat phase was composed of palm fat and rice bran oil and emulsions were produced without emulsifier.…”
Section: Emulsion Gel Products (Margarine and Spread)mentioning
confidence: 99%
“…The esters can be decomposed and converted to obtain biologically active functional substances, 28 alkanols and 30 alkanols, which are U. S. Food and Drug Administration (FDA)-approved functional additives, which can improve mobile endurance and regulate fat metabolism [43]. And lowering cholesterol, it can be widely used in functional foods, various nutritional supplements, medicines, cosmetics and high-grade feeds, and its market share is also expanding [44]. Functional foods with 28 alkanols as the main ingredients are popular in the United States, Japan and other countries.…”
Section: Rice Bran Waxmentioning
confidence: 99%